Navigating morality in gaming: ethical design and behavioral prediction in violent video games - Zainal Azmi, Nurazlin; Hassan, Mohd Khairul Azmi; Amir Hussin, Amir 'Aatieff (Centre for Islamisation & KICT, IIUM, 2024)
With over 90% of video games rated E10+, Teen, and Mature depicting some form of violent imagery, concerns about the potential impact on aggressive behaviour remain highly relevant. The inability of players to distinguish in-game violence from real-world actions can lead to moral panic, indicative of a broader cultural issue. From a game design perspective, it is essential to create games that are entertaining, realistic, and rewarding, allowing players to engage in actions without real-world moral consequences. Game designers shape the game world through rules that guide player behaviour within set constraints. Ethical game design should consider the moral implications of in-game actions, challenging players to make decisions based on their morals and learn from the consequences. This paper reviews the application of AI to predict the behaviour of violent video gamers confronted with moral challenges in video games, and how it can change the course of the story based on the players’ morality demonstrated throughout the game. The insights gained will help game designers to consider developing ethical yet engaging games, while enhancing the moral awareness of players and contributing to societal well-being.